2011
DOI: 10.1111/j.1747-0285.2011.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Quinoxaline Derivatives as Antioxidant and Anti‐Inflammatory Agents

Abstract: .We report the synthesis, anti-inflammatory and antioxidant activities of novel quinoxaline and quinoxaline 1,4-di-N-oxide derivatives. Microwave assisted methods have been used in order to optimize reaction times and to improve the yields. The tested compounds presented important scavenging activities and promising in vitro inhibition of soybean lipoxygenase. Two of the best lipoxygenase inhibitors (compounds 7b and 8f) were evaluated as in vivo antiinflammatory agents using the carrageenin-induced edema mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 36 publications
0
57
0
1
Order By: Relevance
“…LOX is an enzyme essential to arachidonic acid (AA) metabolism, which leads to the formation of leukotrienes, a type of proinflammatory mediator involved in processes like fever, asthma and cardiovascular disease [52]. It was demonstrated that the incorporation of pyrimidine, thiazolopyrimidine, pyrazolopyridine, pyridopyridine, p-chlorophenyl, p-methoxyphenyl or pyridine nucleus to quinoxaline moiety cause significant anti-inflammatory activity, and also analgesic [50].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…LOX is an enzyme essential to arachidonic acid (AA) metabolism, which leads to the formation of leukotrienes, a type of proinflammatory mediator involved in processes like fever, asthma and cardiovascular disease [52]. It was demonstrated that the incorporation of pyrimidine, thiazolopyrimidine, pyrazolopyridine, pyridopyridine, p-chlorophenyl, p-methoxyphenyl or pyridine nucleus to quinoxaline moiety cause significant anti-inflammatory activity, and also analgesic [50].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…[14,15] Our group has vast experience in the synthesis and biological evaluation of multiple quinoxaline 1,4-di-Noxide derivatives, having identified a broad spectrum of anti-infective activities. [16][17][18][19][20][21][22][23][24][25][26] The evaluation of several libraries of compounds led us to find a series with high in vitro activity against T. cruzi. [27] This finding allowed us to establish structural features for maintaining high in vitro activity against the parasite (Scheme 1).…”
mentioning
confidence: 99%
“…Several biological effects have been reported, including anticancer (14,16,17), antimicrobial (18)(19)(20)(21)(22), antiviral (23), and anti-inflammatory and antioxidant (24,25) effects.…”
mentioning
confidence: 99%